The Role of the Scientific Method in Enhancing Student Faith in Aqidah Studies: A Review of Imam Al-Ghazali's Thought - Khoirunisa, Amelia; Aziz , Fachril Achmad; Faizin, Moh. (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: Aqidah learning in higher education plays a vital role in shaping students' faith. However, many students still struggle to apply the aqidah theory to their daily lives. Therefore, the application of scientific methods in aqidah learning is urgently needed to enhance students' understanding and deepen their faith. Objective: This study aims to elucidate the importance of scientific methods in aqidah learning from the perspective of Imam Al-Ghazali. Method: This study employs a literature review, analyzing the works of Imam Al-Ghazali and related literature. Result: The scientific method, which involves a rational and critical approach, enables students to understand faith more deeply and practically. Imam Al-Ghazali emphasizes the importance of integrating faith and morals, which can be strengthened through a scientific approach. Conclusion: The application of scientific methods in the study of aqidah significantly contributes to strengthening students' faith, enhancing the quality of teaching, and fostering a more rational and systematic understanding of religious teachings. Contribution: This study aims to introduce the application of scientific methods in aqidah education, which can serve as a reference for the development of religious curricula and teaching in higher education.